2014
DOI: 10.1155/2014/167438
|View full text |Cite
|
Sign up to set email alerts
|

Obsessive-Compulsive Aspects and Pathological Gambling in an Italian Sample

Abstract: Introduction. Gambling behaviour appears as repetitive and difficult to resist and seems to be aimed at neutralizing or reducing negative feelings such as anxiety and tension, confirming its similarities with the obsessive-compulsive spectrum. Aims. Estimating the prevalence of gambling behaviour in an Italian sample and assessing the effects of sociodemographic variables and the correlations between gambling behaviour and obsessive-compulsive features. Methods. A sample of 300 Italian subjects was evaluated b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…The measurement with the IRI-B could be useful for this predictive value in order to identify those people who manifest a mode of superficial thinking, tending to lack of imaginative and emotional processing, strongly oriented to external reality rather than introspection. Research has shown that, especially in adolescence, such alexithymic components have been associated with various forms of addiction, eating disorders, post-traumatic disorders, abuse and violence suffered (Larsen et al, 2006;Dalbudak et al, 2013;Petruccelli et al, 2014;Strickland et al, 2017;Garofalo et al, 2018;Gillespie et al, 2018;Leshem et al, 2019). In particular, it is necessary to undertake early (after the assessment) with these individuals psycho-educational interventions aimed at improving emotional awareness and affective regulation, in order to allow them to perceive the real state of need related to the emotion experienced and activate the ability to ask for help, comfort, closeness as well as to empathize and understand the feelings and needs of others.…”
Section: Discussionmentioning
confidence: 99%
“…The measurement with the IRI-B could be useful for this predictive value in order to identify those people who manifest a mode of superficial thinking, tending to lack of imaginative and emotional processing, strongly oriented to external reality rather than introspection. Research has shown that, especially in adolescence, such alexithymic components have been associated with various forms of addiction, eating disorders, post-traumatic disorders, abuse and violence suffered (Larsen et al, 2006;Dalbudak et al, 2013;Petruccelli et al, 2014;Strickland et al, 2017;Garofalo et al, 2018;Gillespie et al, 2018;Leshem et al, 2019). In particular, it is necessary to undertake early (after the assessment) with these individuals psycho-educational interventions aimed at improving emotional awareness and affective regulation, in order to allow them to perceive the real state of need related to the emotion experienced and activate the ability to ask for help, comfort, closeness as well as to empathize and understand the feelings and needs of others.…”
Section: Discussionmentioning
confidence: 99%
“…Goubet and Chrysikou's (2019) recent study generally highlights a smaller repertoire of emotional regulation strategies and significantly less flexibility of implementation in males compared to females. Failing to fully accept and cope with their negative states, male students are likely to defend themselves through systematic avoidance, impulsively channeling their energies into social, sporting, playful, virtual, video games, and gambling activities, thereby distancing themselves from the academic task (Zhong, 2013;Petruccelli et al, 2014;Nordby et al, 2019;Shi et al, 2021). This impulsive tendency towards self-distraction and defocusing progressively lowers the level of engagement and motivation to study (Wypych et al, 2018;Svartdal et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…However, there is some evidence militating against a strong relationship between gambling disorder and OCD. In a community sample, gambling disorder symptoms correlated negatively rather than positively with obsessive-compulsive symptoms (Petruccelli et al 2014). …”
Section: Comorbiditymentioning
confidence: 98%